Combining Cobalt‐Assisted Alkyne Cyclotrimerization and Ring Formation through C–H Bond Activation: A "One‐Pot" Approach to Complex Multimetallic Structures. Issue 26 (20th August 2014) - Filipczyk, Grzegorz; Hildebrandt, Alexander; Pfaff, Ulrike; Korb, Marcus; Rüffer, Tobias; Lang, Heinrich
Abstract: Multiferrocenyl‐substituted benzenes could be obtained in a "one‐pot" reaction of 1, 4‐diferrocenylbutadiyne with substoichiometric amounts of [CoCp(CO)2 ] (Cp = cyclopentadienyl) by combining cobalt‐assisted formal [2+2+2] cycloaddition with C–H bond activation at a single catalyst. A mechanism for the reaction is discussed. The newly synthesized hexaferrocenyl species belongs to the rather scarcely examined family of multimetallic aromatic compounds. It is one of the few examples in which the ferrocenyl units are either single bonded or 1, 2‐substituted to give rise to planar chirality at three of the ferrocenyl units. Electrochemical studies showed that up to six consecutive ferrocenyl‐based redox events are observed. Within in situ spectro‐electrochemical measurements of both compounds it is shown that two intervalence charge‐transfer pathways are possible. At different excitation energies either a charge transfer through the peripheric ethylene bridging unit or through the central benzene unit occurs. Abstract : A straightforward one‐pot synthetic method including cyclotrimerization, C–H activation, and ring formation to novel hexaferrocenylbenzene is discussed. The electrochemical and spectro‐electrochemical behavior as well as a mechanism for the formation of the title compound is reported.